Sterba's Problem of Evil vs. Sterba's Problem of Specificity: Which Is the Real Problem? - Jones, Michael S. (Religions, 2022)
In 2019 the noted ethicist and political philosopher James Sterba published a new deductive version of the argument from the problem of evil to the conclusion that an Anselmian God does not exist. In this article I will argue that Sterba’s argument involves a problematic sorites-type paradox that, in order to be consistent, he should view as undermining his argument, since in his previous work on ethics he viewed this same sort of problem as counting as a significant objection to moral cultural relativism. I show how his arguments involve a sorites-like paradox, explain how this is damaging to the argument from evil, and conclude by offering suggestions for how Sterba might address this weakness.